Bench, bed and beyond: Communication and responsibility in decentralised tuberculosis care - Jennifer Watermeyer; Claire Penn; Megan Scott; Tshegofatso Seabi (AOSIS, 2019)
Background: South Africa faces one of the world's worst drug-resistant tuberculosis epidemics. Implementing successful care in this context has proven challenging for a number of reasons. Communication is an essential yet neglected feature of care and research in the field of tuberculosis. Aim: The primary aim of this qualitative study was to explore communication facilitators and barriers at several tuberculosis care sites. In this article, we focus on communication practices across the chain of diagnosis, treatment, discharge and follow-up in decentralised care approaches and present evidence of gaps in communication. Setting: The study was conducted at three tuberculosis care sites in two South African provinces. Methods: Participants included healthcare workers, patients, community members and home-based carers. Data included 79 interviews, 4 video-recorded interactions between patients and healthcare workers, and ethnographic observations at each site. We analysed the data using thematic analysis and a qualitative sociolinguistic framework. Results: Communication in decentralised care contexts is complex because of multiple sites and role players. Responsibility for communication seems to be unduly placed on patients, treatment guidelines are not implemented consistently across sites and assumptions are made about the role of others in the chain. Patient and healthcare worker reports suggest confusion and frustration. Conclusion: Communication in the South African tuberculosis care context appears fragile and current mechanisms for detecting flaws in the care chain are not sensitive to communication issues. We make recommendations for strengthening home-based care resources, providing team training and focusing on communication processes in monitoring and evaluating systems.